Longitudinal follow-up of SWEDD subjects in the PRECEPT Study - Marek, Kenneth; Seibyl, John; Eberly, Shirley; Oakes, David; Shoulson, Ira; Lang, Anthony E; Hyson, Chris; Jennings, Danna (Neurology, 2014)
To compare the clinical and imaging characteristics of those PRECEPT (Parkinson Research Examination of CEP-1347 Trial) subjects with a scan without evidence of dopaminergic deficit (SWEDD) to those with dopamine transporter (DAT) deficit scans at study baseline and during a 22-month follow-up. Baseline (n = 799) and 22-month follow-up (n = 701) [(123)I] β-CIT SPECT scans were acquired. The percent change in [(123)I] β-CIT striatal binding ratio, the percentage of subjects requiring dopaminergic therapy, the change in Unified Parkinson's Disease Rating Scale (UPDRS) score, and the PRECEPT Study investigators' diagnosis at study termination were compared between SWEDD and DAT deficit subjects. SWEDD subjects (n = 91) compared with DAT deficit subjects (n = 708) showed reduced UPDRS score at baseline (18.7 [SD 8.5] vs 25.5 [SD 10.5], p < 0.05) and minimal change in both [(123)I] β-CIT striatal binding ratio (-0.2% [SD 12.2] vs -8.5% [SD 11.9], p < 0.0001) and UPDRS score (0.5 [SD 6.9] vs 10.5 [SD 8.9], p < 0.0001) at follow-up assessments. At PRECEPT termination, the diagnosis by study investigators was changed from Parkinson disease (PD) to other disorders not associated with DAT deficit in 44% (95% confidence interval 34.2, 54.7) of SWEDD subjects compared with 3.6% (95% confidence interval 2.3, 5.1) of DAT deficit subjects. These results indicate that subjects identified as having a SWEDD, with DAT imaging within the normal range, have minimal evidence of clinical or imaging PD progression. These data strongly suggest that SWEDD subjects are unlikely to have idiopathic PD.